Load frequency control of time-delayed power systems using optimal IMC-PID design and model approximation approach. (3rd September 2022) - Ganji, Vasu; Ramraj, Ch. Bharath naga
ABSTRACT: In this paper, a new optimal and robust IMC-PID control design is proposed for the LFC of time-delayed power systems. The proposed design is a process reduction control approach. Primitively, a simple and approximate model (i.e. Reduced Order Model (ROM)) is determined for the large-scale power system by using the proposed Enhanced Differential Evolution (EDE) algorithm-based Model Order Reduction (MOR) approach. Further, by considering the ROM as an internal plant model, the unknown IMC filter time constant is tuned to attain the optimal performance by minimizing the integral of error between the reference input and the actual output responses of the power system by using the EDE algorithm. Finally, the finest PID controller gains are determined by the least-square model matching with the optimal IMC. The proposed design is illustrated by applying to various Single-Area Power Systems (SAPS) with a delay between the power system sensing device to the control centre. The simulation results demonstrate the efficacy of the proposed IMC-PID design in improving the dynamic stability against consistent and inconsistent delays and the robustness towards the load disturbances, parameter uncertainties and model mismatches.